Analysis of Auli’i Cravalho’s Character Related To Liberal Feminism In Moana Disney Movie By Ron Clements And John Musker - Murtadho, abdul Muhid; Yulianda, Lingga; Fasikh, Mukhlasul; Sitepu, Julyanta Br (STIBA IEC JAKARTA, 2024)
This research focuses on analyzing characterisctic of Auli’s Cravalho’s related to liberal feminism in Moana Disney Movie. The writer uses a qualitative descriptive approach with collect data through Moana Movie. This research is aimed at finding how Auli’i Cravalho’s Characters (as Moana) in Moana Disney Movie, showing the action of Auli’i Cravalho’s (as Moana) to defend her rights as woman in Moana Disney Movie, and explain the scenes showing the character of liberal feminism. The result of the research shows that the six (6) total character positive in Moana Movie, four (4) total character negative in Moana Movie, five (5) action showing liberal feminism. And nine (9) showing scenes related to liberal feminism. Based on the analysis, the writer hope a journal on the film Moana related to liberal feminism is expected to provide valuable insights or significant contributions to the study.